Franchising as strategy for internationalization of Family Firms: an exploratory study - Rosado-Serrano, Alexander (2017)
Family business is the most prevalent form of business thru out Latin America. Franchising has been a strategy used by many firms to expand domestically and internationally. Internationalization theories indicate that firms tend to expand to culturally close markets/countries. Family Business theories indicate that family firms have specific advantages in comparison with non-family firms. The purpose of this paper is to conduct a literature review about franchising family firms in Latin America to develop a theoretical model for their internationalization process using franchising.